Managing Change and Finding Identity: A Grounded Analysis of Advertising Agency Leadership. Issue 3 (2nd September 2019) - Patwardhan, Padmini; Habib, Sabrina; Patwardhan, Hemant
Abstract: This study is one of the first to examine advertising leadership as agencies adapt to the knowledge era. Using grounded-theory methodology (GTM) analysis, it explores how effective leadership is viewed, articulated, and practiced in a period of change in contemporary United States-based ad agencies. In-depth interviews with 16 leaders led to formulation of a grounded theory of agency leadership with three interdependent core concepts: managing change, finding identity, and leading effectively. Successful leadership at the agency is a process of negotiation, adaptation, and collaboration. Negotiating external change poses numerous internal challenges and adaptation: talent flight, internal turf wars, and cultural shifts in agency composition. Leaders must demonstrate capability through both being (qualities) and doing (actions) and lay equal emphasis on performance (product) and human capital (people). Leaders' change management abilities, hard and soft skills, collaborative vision, and managerial pragmatism are key to agency success. Future research may explore topics like leadership and agency culture, global contexts of agency leadership, and issues in leadership training.